2010
DOI: 10.1002/ajmg.a.33381
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of the sella turcica in velocardiofacial syndrome suggests involvement of a neural crest developmental field

Abstract: We described the morphology of the sella turcica in individuals with velocardiofacial syndrome (VCFS), also known as chromosome 22q11.2 deletion syndrome, and compared the morphology with that of a control group of individuals from the Oslo University Craniofacial Growth Archive. The aim was to measure the cranial base angles in individuals with VCFS and, if possible, to discover the developmental field that may be involved in the condition. The study included 33 patients with VCFS from the Copenhagen Cleft Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 46 publications
1
31
0
2
Order By: Relevance
“…The phenotypical presentation of human neurocristopathies commonly includes features that have been described in domesticated mammals [Sánchez-Villagra et al, 2016]. Interestingly, well-defined neurocristopathies like velocardiofacial syndrome (OMIM #192430) and DiGeorge syndrome (OMIM #188400) involve schizophrenic features [Mølsted et al, 2010;Zhang et al, 2014;Escot et al, 2016]. Likewise, given the NC derivation of most craniofacial structures, the craniofacial abnormalities observed in SZ are believed to result from disturbances in neuroectodermal development, hence representing putative external biomarkers of atypical brain growth [Compton et al, 2007;Aksoy-Poyraz et al, 2011] and suggesting an additional connection between SZ and domestication at the level of NC functional implications.…”
Section: Other Featuresmentioning
confidence: 99%
“…The phenotypical presentation of human neurocristopathies commonly includes features that have been described in domesticated mammals [Sánchez-Villagra et al, 2016]. Interestingly, well-defined neurocristopathies like velocardiofacial syndrome (OMIM #192430) and DiGeorge syndrome (OMIM #188400) involve schizophrenic features [Mølsted et al, 2010;Zhang et al, 2014;Escot et al, 2016]. Likewise, given the NC derivation of most craniofacial structures, the craniofacial abnormalities observed in SZ are believed to result from disturbances in neuroectodermal development, hence representing putative external biomarkers of atypical brain growth [Compton et al, 2007;Aksoy-Poyraz et al, 2011] and suggesting an additional connection between SZ and domestication at the level of NC functional implications.…”
Section: Other Featuresmentioning
confidence: 99%
“…Some have reported platybasia in patients with 22q11DS with respect to a control group [5,6,7,13,19,20]. Others have used cut-off values, defining platybasia as 7° [21] or 10° [16] above the normal mean without specifying SDs.…”
Section: Discussionmentioning
confidence: 99%
“…Mølsted et al [5] suggested a failure of or aberrant migration of the neural crest during the fourth week of embryogenesis. The defective migration of these cells leads to the syndrome which is associated with variable findings that are, as exemplified by our case, not always clinically pronounced.…”
Section: Discussionmentioning
confidence: 99%